UNVEILING FEMALE OBJECTIFICATION IN SOFIA ISELLA’S DOLL PEOPLE: A CRITICAL DISCOURSE ANALYSIS - Nissa Nursasi Fatika; Dewi Sri Kuning (Lire Journal (Journal of Linguistics and Literature), 2026)
This study aims to examine the representation of women and power relations in the song “Doll People” by Sofia Isella using Norman Fairclough’s Critical Discourse Analysis (CDA). This qualitative study uses song lyrics obtained from the official Spotify platform as verbal data, analyzed through Fairclough’s three-dimensional framework: text, discourse practice, and social practice. The findings indicate that, at the textual level, women are represented as objects through metaphors, passive constructions, and identity labeling, reflecting patterns of dehumanization and fragmentation. At the level of discourse practice, meaning and identity are constructed through external perspectives that position women as objects of observation and evaluation. At the level of social practice, the lyrics reflect unequal power relations associated with patriarchal ideology, while also presenting elements of resistance through a shift toward agency. This study suggests that song lyrics function as a discursive space where objectification is both reproduced and questioned, contributing to a deeper understanding of gender representation in contemporary music.